Pembinaan Keagamaan pada Eks-Pasien Gangguan Jiwa di Lembaga Ngundi Rahayu Paringan Jenangan Ponorogo - Mahmudin, Afif Syaiful (Tapis: Jurnal Penelitian Ilmiah, 2021)
A mental disorder has been occurring in Ponorogo Regency. Based on a survey conducted by the Psychiatric hospitals of Malang and the Ponorogo Regional Government (2011) revealed that 60 people in Paringan Village have suffered mental disorders and were treated in a Psychiatric Hospital. However, the mental disorder patients would not be fully recovered from treatment and needed rehabilitation, whereas their families were mostly reluctant to accept them back. According to this problem, Ngudi Rahayu Institution in Paring was established to rehabilitate and provide intensive religious guidance to the ex-mental disorders patients for preparing them for socializing. This phenomenological research approach was conducted to expose religious subjects employed by Ngudi Rahayu Institute for rehabilitating ex-mental disorders patients and how does it implement, and its effect on mental health improvement. This study resulted that religious guidance subjects were adjusted with the patient's condition. Furthermore, its implementation was carried out by medical personnel and occupational therapy. The religious development strategy did not only focus on the patients but also the supervisor by increasing their religious knowledge competence. The effect of religious guidance on improving mental health is very significant, as the number of patients who had recovered and been successfully discharged with a stable and healthy mental state.